Pengaruh Kepuasan dan Kepercayaan Pelanggan terhadap Loyalitas Pelanggan dalam Berbelanja - Ningrum, Rosi Setia; Hermana, Cecep (BUDGETING : Journal of Business, Management and Accounting, 2024)
This research aims to assess the impact of customer satisfaction and trust on loyalty in E-commerce shopping in Indonesia. This study employs a research methodology based on a literature review. The participants of this study include individuals who have engaged in online shopping through various e-commerce platforms such as Tokopedia, Shopee, Lazada, Blibli, and others. The investigation findings indicate that customer satisfaction influences consumer trust and customer loyalty during the e-commerce purchase process. Hence, it is crucial for online business proprietors to consistently enhance client happiness and trust to stay competitive with rivals and ensure the sustainability of their firm. Keywords: Customer Loyalty, Customer Satisfaction, Customer Trust, E-commerce